1986
DOI: 10.1520/jfs11883j
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Diagnosis from Frozen Canine Tissues

Abstract: Frozen tissues were studied microscopically to determine their value for diagnostic purposes. Sections were taken from lung, liver, kidney, small intestine, and brain of ten diseased dogs that died or were euthanatized. Some tissues were frozen, held for two or seven days, and then formalin-fixed. Tissues that were formalin-fixed immediately served as controls. Freezing changes such as transudate, cell shrinkage, fractures, hemolysis, and hematin formation were a nuisance, but usually did not prevent making a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This is perhaps because the frozen artifact is easily identified in other organs such as liver, making examination of muscles unnecessary. 1,2,19 Other than the brain, structural changes in the solid organs of fish were either not present or not as distinct as in mammals. Therefore, coelomic viscera does not seem to be a useful indicator of freeze-thaw in fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is perhaps because the frozen artifact is easily identified in other organs such as liver, making examination of muscles unnecessary. 1,2,19 Other than the brain, structural changes in the solid organs of fish were either not present or not as distinct as in mammals. Therefore, coelomic viscera does not seem to be a useful indicator of freeze-thaw in fish.…”
Section: Discussionmentioning
confidence: 99%
“…1,15,19 Freeze artifact in boney fish has been infrequently and incompletely documented, with most studies focusing on freezing as it relates to commercial food storage. [1][2][3][4]6,11,14,16 Frozen storage of food fish causes macroscopic changes in muscle color, texture, and weight due to fluid loss, ice crystal formation, and bacterial growth. 4,9 These changes are somewhat subjective, require comparison to the tissue before storage, and may differ with species and seasonality.…”
mentioning
confidence: 99%
“…Very few studies have focused on the effect of freezing cadavers prior to placing them in experimental contexts . Some histological studies have examined changes in the cellular matrix after freezing, with findings suggesting that freezing changes the appearance of the cellular matrix, but did not affect the overall ability to distinguish tissue types . For decomposition studies, Micozzi found that animal cadavers frozen prior to study began initial decay via aerobic (or outside in) decomposition, rather than anaerobic decomposition or putrefaction (or inside out) as is typical in fresh cadavers.…”
mentioning
confidence: 99%